Technological leadership and sectorial employment growth: A spatial econometric analysis for U.S. counties - Pede, Valerien O.; Florax, Raymond J. G. M.; de Groot, Henri L. F.; Barboza, Gustavo (Wiley, 2021)
This paper studies the determinants of technological catch‐up considering spatial and sectoral aggregation of industries. We investigate how geographical and technological proximity to the technology leader impact regional employment growth. We model technological progress by means of a hierarchical process of catch‐up to the technology leader. We also incorporate measures for knowledge spillover effects to test the roles of competition, specialisation, and diversity at the industry level. Empirical results using data at the county level for different economic sectors (2‐dig NAICS) for the United States indicate that human capital plays a crucial role in promoting sectoral employment growth. The association between technological/geographical distance to the technology leader and employment growth varies across sectors.